Delivery of Radioiodine Ablation in a Patient with End-Stage Renal Disease - Bussey, Andrew T.; Tin, Aung; Hoye, Neil; Richardson, Mark (World Journal of Nuclear Medicine, 2022)
This case presents a pragmatic approach to the management of a radioiodine remnant ablation patient on hemodialysis which required no pretherapeutic dosimetric measurements. Pretreatment radiation dose modeling was performed using literature values for radioiodine hemodialysis extraction efficacies to determine a safe treatment regimen including adjustment of the administered activity and hemodialysis frequency. The pretreatment modeling was subsequently verified using external and blood radiation monitoring during treatment.
Keywords: thyroid carcinoma; I-131; hemodialysis; end-stage renal disease